Sustainable Strategies for the Dynamic Equilibrium of the Urban Stream, Cheonggyecheon. (April 2018) - Seo, D; Kwon, Y
Abstract: Cheonggyecheon, which had been transformed into a 14-lane urban highway and a large underground sewer system, was finally converted back to an urban stream again. Its transformation has been praised as a successful example of urban downtown regeneration and beautification. It is, however, obvious that there have not been prudent ecological considerations since the project's principal goals were to provide public recreational use and achieve maximum flood control capacity via the use of embankments. For a healthier and sustainable stream environment, Cheonggyecheon should be ecologically re-restored again, based on a dynamic equilibrium model. It must primarily establish a corridor of vegetation, an aquatic transitional zone, and install constructed wetlands nearby which support the water source. The upper streams of Cheonggyecheon should be further restored and supply natural waters. Furthermore, there ultimately needs to be de-channelization for hydrological sustainability. This would vary from merely increasing the sinuosity to thoroughly reconstruct a naturalized stream. Complete dynamic equilibrium of Cheonggyecheon can be accomplished through more fundamental sustainable strategies.